Um ambiente de autoria para aplicações com realidade aumentada - Fraga, Thiago Zamborlini (2017)
This work presents an Augmented Reality Authoring Environment system, named A3RA, based on current technologies and concepts, for mobile devices use, bringing a new approach to multi-platform mobile systems with access to application server, so there is a minimum of effort with the technology use by teachers and students on teaching and learning area. The A3RA is composed of a web environment where the teacher, from his planning content, inserting multimedia objects, configuring events when these objects will activate, organizes the class, inserting his scripts and his objects into a technologically structured system, and a client environment where the students experience the use of Augmented Reality (AR), which was designed by the teacher. Then, this technology must be incorporated into the pedagogical process because it is a powerful educational process ally, generating numerous of transformations and allowing a greater approximation with the students reality who grow up using environments rich in multimedia resources, with different expectations of previous generations. The work realization starts from the desire to seek solutions that may contribute to the reduction of past difficulties in the author student life, seeking in technology, support to propose technological alternatives, as support for student learning so that they may be more involved in their own learning, and that the contents become more interesting for them. AR provides for the students experiences that allow them to merge the real world with the virtual world, which leads them to participate in real-world exploration using virtual objects such as texts, videos, and images that are complementary elements for conduct the real-world investigations for the students. AR systems are used to present lessons that would otherwise not be possible, so that learners could virtually manipulate a variety of learning objects and manipulate information in an innovative and interactive way. Mobile devices and their sensors provide opportunities that enhance learning. The work was based on bibliographical studies and related works analysis on the understanding way what already exists in the market and the successful experiences with the AR use in teaching and learning, as well as the analysis and tools evaluation for the system development. With the system prototype, internal tests were performed to validate the stability or performance of the technologies used, with minimum of errors for application. The final system of the A3RA has been reached, with few limitations, which doesn’t invalidate the application, which has the intention to contribute for the student learning and assist the teacher with innovative tools.